Managing Online Promotion Media to Enhance Marketing Performance of Batik Bag Crafting Sme ‘Batika Indonesia’ in Yogyakarta - Harsoyo, Titik Desi; Nuvriasari, Audita; Kusuma, Nala Tri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This community service is carried out in Batika Indonesia, a SME in Yogyakarta which produces mainly batik handmade bags. It is located on Jl. Matraman No.4-24, Nanggulan, Maguwoharjo, Yogyakarta. As the potential crafting company in Yogyakarta, Batika Indonesia faces high competition. This condition requires Batik Indonesia to increase its marketing performance through managing online promotion media. Based on the situation analysis, it was found some problems in online promotion, namely the lack of management of online promotion media. Therefore, the purpose of this community service activity is to help partner to solve the problems through three programs. First, update the website content to enhance the website appearance with more attractive and informative content. Second, provide training to advance the management of online promotion media mainly focus on Instagram and TikTok. Third, make e-catalogue to provide customer a more informative and complete file to make it easier and faster for customers to find information about the latest products. The training is expected to increase partner’s knowledge and skills regarding managing online promotion media. Finally, it will help Batika Indonesia to improve its marketing performance. It is hoped that there will be continuity of the trainings where partner can implement and develop online promotion media in the future.